Exploring the molecular mechanism of notoginsenoside R1 in sepsis-induced cardiomyopathy based on network pharmacology and experiments validation - Shao, Ruifei; Li, Wei; Chen, Rui; Li, Kunlin; Cao, Yu; Chen, Guobing; Jiang, Lihong (Frontiers in Pharmacology, 2023)
Sepsis-induced cardiomyopathy (SIC) is an important manifestation of sepsis, and abnormal cardiac function affects the development of sepsis. Notoginsenoside R1 (NG-R1) is a unique bioactive component of Panax notoginseng with anti-inflammatory and antioxidant effects. However, the effects and possible mechanisms of NG-R1 on SIC are not clear. The purpose of this study was to identify the potential targets and regulatory mechanisms of the action of NG-R1 on SIC. To investigate the potential mechanism, we used network pharmacology, molecular docking, qRT-PCR, and immunofluorescence. The results showed that NG-R1 ameliorated myocardial fibrosis in septic mice. Validation of network pharmacology and molecular docking results revealed that NG-R1 reduced tumor necrosis factor-Alpha (TNF-α) expression in myocardial tissues and AC16 cardiomyocytes in mice, as well as inflammatory factor release in AC16 cells, so TNF-α may be a potential target of NG-R1 against SIC. The present study demonstrated that NG-R1 could protect against SIC and by regulating the expression of TNF-α inflammatory factors, providing a new idea for sepsis drug development.